Local and sub-regional socio-economic and environmental impact of large-scale resort development - Van der Merwe, Schalk Willem Jacobus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Geography and Environmental Studies))--University of Stellenbosch, 2006.